Stress testing credit risk: experience from the italian FSAP - Laviola, Sebastiano; Marcucci, Juri; Quagliariello, Mario (PSL Quarterly Review, 2012)
In this paper we describe the methodologies that can be used for stress testing credit risk providing some applications to the Italian banking system.Within the FSAP for Italy, stress tests examined the impact of a variety of shocks on the nine major Italian banking groups. The tests were performed using both top-down and bottom-up approaches, which provided comparable results. For the sensitivity analysis, the size of the shocks to assess market risk, sovereign risk, interest rate rÌsk in the banking book and liquidity risk was in line with those ap-plied in other FSAPs for euro area countries, while the credit risk shock exceeded the largest historical shock. In addition, the impact of various adverse macroeconomic scenarios has been assessed. Specifical-ly, an adverse macro scenario in which oil prices reach USD 85-90 per barrel causing a global slow down and global equity prices decrease by 30% has the largest impact. Overall, stress test results suggest that the Italian banking sector is resilient to shocks. Profits appear in most cas-es sufficient to cover 10sses arising from the shocks calibrated. Existing capitaI buffers remain comfortably above the minimum regulatory sol-vency ratios. The implementation of macroeconomic stress-testing pro-grammes such as those underlying the FSAPs has advanced the devel-opment of internally consistent stress testing procedures. However, the state of the art is still evolving and further work in this field will allow relaxing less realistic assumptions, further improving the methodologies and making results more reliable. JEL Codes: G11, G18, G21, G28